2001
DOI: 10.1038/sj.bjp.0704411
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of antigen‐induced airway inflammation and airway hyper‐responsiveness in low affinity neurotrophin receptor p75 gene deficient mice

Abstract: 1 Recently, much attention has been paid to the relationship between the nervous and immune systems. The present study was conducted to clarify the role of neurotrophin low anity receptor (p75N) in allergic airway in¯ammation and hyper-responsiveness (AHR) in mice by employing p75N gene de®cient mice. 2 Mice were immunized twice by intraperitoneal injections of ovalbumin (OA) at intervals of 12 days. OA was inhaled 10 days after the secondary immunization and repeated three times at 4 days interval. Twenty-fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…There are two NGF receptors: the higher-affinity TrkA receptor and the lower-affinity receptor p75 (p75NTR). The relative contribution of these two receptor types to asthma is not completely clear, although airway hyperreactivity has been associated with either receptor (16,31,46). It may also be significant that TrkA and p75NTR are expressed by eosinophils (37) and parasympathetic nerves (28), both of which are potential targets for NGF.…”
Section: Discussionmentioning
confidence: 94%
“…There are two NGF receptors: the higher-affinity TrkA receptor and the lower-affinity receptor p75 (p75NTR). The relative contribution of these two receptor types to asthma is not completely clear, although airway hyperreactivity has been associated with either receptor (16,31,46). It may also be significant that TrkA and p75NTR are expressed by eosinophils (37) and parasympathetic nerves (28), both of which are potential targets for NGF.…”
Section: Discussionmentioning
confidence: 94%
“…Different animal models have been developed in order to investigate the therapeutic effect of NSO on allergic asthma thus far. However, we selected our model as it shows all the salient features of allergic airway inflammation in humans including increased serum antigen-specific IgE, increased Th2 cytokine levels and decreased Th1 cytokine levels in BALF, enhanced airway responsiveness to Ach, airway eosinophilic inflammation, and goblet cell hypertrophy and hyperplasia [27,28]. The results of our study showed that oral treatment with NSO in mice sensitized and challenged with OVA significantly improves AHR, decreases the number of total leukocytes, macrophages and eosinophils, levels of IL-4, IL-5 and IL-13 in BALF, serum levels of total IgE, OVA-specific IgE and IgG1, and significantly increases the level of IFN-γ in BALF and serum level of OVA-specific IgG2a with abrogation of histological changes in lung tissues in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The bronchial hyper-reactivity of asthma is accompanied by an increase in NGF, probably produced by mononuclear cells, which enhances local Th2 responses, thereby increasing the production of IL-4, IL-5, IgG1 and IgE, but not IFN-γ nor IgG2 (Braun et al 1998). Some of these responses may be mediated by p75 NTR acting on Th2 cells (Tokuoka et al 2001). Moreover, systemic NGF administration increases histamine-induced bronchial hyper-reactivity; this effect is probably mediated by tachykinins because it is abolished by a neurokinin-1 receptor antagonist, and may be exerted indirectly, via macrophages or mast cells (de Vries et al 1999).…”
Section: Pathologies Associated With Changes In the Neurotrophin Systemmentioning
confidence: 99%